Pembentukan Kelompok Sebaya sebagai Upaya Mencegah HIV/AIDS pada Remaja - Muji Lestari; Fachry Amal; Ellen R.V Purba (Poltekkes Kemenkes Kendari, 2023)
As part of efforts to prevent HIV/AIDS among adolescents, especially high school students, it is considered important to approach using educational strategies through peer groups. This community service activity was carried out at Jayapura City High School in a group of teenage secondary education students. Community Service was carried out in August 2022 by conducting education and training on HIV/AIDS using pocket books in the Papuan language and forming peer groups. The results of the activities were measured using a knowledge questionnaire. There are differences in knowledge before and after providing education and education to community service participants.